Valsalva maneuver procedures in the diagnosis of right-to-left shunt by contrast-enhanced transcranial doppler using agitated saline solution with blood as a contrast agent Manobra de Valsalva no diagnóstico de embolia paradoxal pelo doppler transcraniano contrastado com o uso de solução salina agitada associada a sangue como meio de contraste - Marcos Christiano Lange; Viviane Flumignan Zétola; Elcio Juliato Piovesan; Lineu César Werneck (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To compare two different timings for the performance of the Valsalva maneuver (VM) using an infusion of agitated saline solution with blood as contrast agent (CA) to right-to-left shunt (RLS) screening. METHOD: 42 patients were submitted to a standardized contrast-enhanced transcranial doppler (cTCD) to screen for right-to-left shunt (RLS). cTCD technique was done with two different moments of the VM: [1] the CA injection during the VM (CAduringVM test); [2] the CA injection before the VM (CApreVM test). RESULTS: Positive MCA tests were observed in 47 (56%) CAduringVM tests and in 50 (59.5%) CApreVM tests, p=0.64. There was an almost perfect agreement for the positive tests between the CAduringVM and CApreVM test, r s=0.829 (95% CI 0.61-1.00, p<0.001). CONCLUSION: The present study demonstrates that there is no significant difference in the results of RLS screening by cTCD when two different moments of VM were done. OBJETIVO: Comparar dois momentos diferentes da manobra de Valsalva (MV) com o uso de solução salina com sangue como meio de contraste (MC) para investigação de embolia paradoxal (EP). MÉTODO: 42 pacientes foram submetidos a protocolo padronizado de DTCc com a MV em dois momentos diferentes: [1] injeção do MC durante a MV (teste ACduranteMV); [2] injeção de MC antes da MV (teste ACpreMV). RESULTADOS: Exames positivos foram observados em 47 (56%) ACMs testes ACduranteMV e 50 (59.5%) testes ACpreMV, p=0.64. Houve uma correlação quase perfeita entre ambos os testes, r s=0.829 (95% CI 0.61-1.00, p<0.001). CONCLUSÃO: O presente estudo demonstra que não existe diferença significativa na positividade de EP pelo DTCc quando são comparados dois momentos diferentes da MV.